Peran pemasaran digital dan modal usaha dalam meningkatkan pendapatan: studi empiris pada UMKM di Desa Bandar Tengah Kecamatan Bandar Khalifah - Hadi, Ibnu; Tobing, Yuni Artha Teresia Lumban; Hartanto, Bobby; Mardayanti, Imelda (Journal of Management and Digital Business, 2025)
The development of digital technology and the availability of business capital are two key factors in increasing the income of MSMEs. This research aims to determine the influence of digital marketing and business capital on the income of MSMEs in Bandar Tengah Village, Bandar Khalifah District. The approach used is quantitative, with primary data obtained through the distribution of questionnaires and secondary data derived from relevant literature. The number of respondents was 35 MSME actors using a total sampling technique. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) version 3.0 method. The research results indicate that digital marketing has a substantial impact on the income of MSMEs. Apart from that, business capital has also been proven to have a significant effect on income. These findings confirm that both digital marketing and individual business capital have an important role in increasing MSME income. Therefore, support in the form of digital training and easy access to capital is essential to encourage sustainable business growth.